Exploratory Study on Plasma Immunomodulator and Antibody Profiles in Tuberculosis Patients - Ravindran, Resmi (American Society for Microbiology, 2013)
Host immune responses to Mycobacterium tuberculosis are generally able to contain infection and maintain a delicate balance between protection and immunopathology. A shift in this balance appears to underlie active disease observed in about 10% of infected individuals. Effects of local inflammation, combined with anti-M. tuberculosis systemic immune responses, are directly detectable in peripheral circulation, without ex vivo stimulation of blood cells or biopsy of the affected organs. We studied plasma immunomodulator and antibody biomarkers in patients with active pulmonary tuberculosis (TB) by a combination of multiplex microbead immunoassays and computational tools for data analysis. Plasma profiles of 10 immunomodulators and antibodies against eight M. tuberculosis antigens (previously reported by us) were examined in active pulmonary TB patients in a country where TB is endemic, Pakistan. Multiplex analyses were performed on samples from apparently healthy individuals without active TB from the same community as the TB patients to establish the assay baselines for all analytes. Over 3,000 data points were collected from patients (n = 135) and controls (n = 37). The data were analyzed by multivariate and computer-assisted cluster analyses to reveal patterns of plasma immunomodulators and antibodies. This study shows plasma profiles that in most patients represented either strong antibody or strong immunomodulator biomarkers. Profiling of a combination of both immunomodulators and antibodies described here may be valuable for the analysis of host immune responses in active TB in countries where the disease is endemic.